A PERCEPTUAL CUE ON A MOVING OPPONENT IMPROVES THE LEARNING OF A MOTOR SKILL FROM AIKIDO - Estefan Gemas Neto; Sergio Roberto Silveira; Marcos Antônio Mattos dos Reis; Umberto Cesar Corrêa (Journal of Physical Education)
ABSTRACT The effect of different instructional foci on the learning of a motor skill of aikido was investigated. Sixty participants from both sexes with an average age of 14 practiced choku tsuki task, which consisted of hitting a target on the chest of an attacking opponent with a stick. They were divided into four groups: relaxation, with a cue about the relaxed way in which the task should be performed; low hip, with a cue about maintaining hip displacement as low as possible; perceptive, with a cue at the circular target located on the chest of the opponent as they raised their sword to attack; and control, without cues. The dependent variables included measures related to the task goals, movement pattern relative to the task components and kinematic features. Only the perceptive and low hip groups learned the motor skill. The perceptive group obtained better overall performance than the other groups. Learning choku tsuki was improved by the instructional cue “strike target as soon as sword is raised”, establishing the learner’s perceptive attunement to the moving opponent. Learning was also enhanced by the cue "keep hips as low as possible"; however, at a lower level than that of the perceptive cue.